Grey Parrots Psittacus erithacus in Kampala, Uganda – are they becoming suburbanised?. (20th May 2016) - Irumba, Immaculate-Odd; Pomeroy, Derek; Perrin, Michael
Abstract : The globally Vulnerable Grey Parrot ( Psittacus erithacus ) has been seen in Kampala, Uganda's capital city, in increasing numbers in recent years. This apparently new behaviour of a typically forest species is helped by the presence of many large trees, which provide roosting and nesting sites, and fruiting trees where they feed. Grey Parrots in Kampala potentially come from three sources: escapees, releases of captive birds or wild birds moving into a suburban environment. Birds mostly exhibit behaviours typical of wild birds, but as most, if not all, of the Grey Parrots in captivity are wild-caught and would revert to wild-caught behaviours when released, it is difficult to distinguish them from the wild population. However, we believe that at least some of the birds seen in Kampala are wild.